Antecedents of Halal Brand Equity : A Study of Halal Food Sector of Malaysia - Sharizal, Hashim; Khan, Mussadiq Ali; Iqbal, Asim (Emerald Publishing, 2021)
Purpose - Islamic marketing is an emerging field with a lot of potentials, so it is worthwhile to explore it. This study aims to conduct research on the unexplored relationship of antecedents of the equity, image, and consumers’ trust and satisfaction of halal brands. Design/methodology/approach - A structured questionnaire was designed to conduct research to analyze the halal brand equity and its antecedents. Data were collected from 250 halal consumers of Kota Samarahan and Kuching, Malaysia through a self-administered questionnaire using a convenience sampling method. Findings -The study finds a positive relationship of three antecedents of brand equity which confirms a strong relationship between the image and satisfaction of halal brand equity. The results further showed that halal brand image is linked with halal brand trust but the relationship between halal brand trust and its equity could not be proved. Originality - Islamic marketing has received great attention of researchers, academicians, and practitioners which has rather been unexplored earlier particularly the relationships among antecedents of the equity, image, and consumers’ trust and satisfaction of halal brands. Research Limitations -This has been a cross-sectional study that was limited to Malaysia, a Muslim majority country. Researchers can conduct a longitudinal study and can conduct it in non-Muslim societies to comprehend their diversity and wider impact. Additionally, this study was limited to halal food brands in Malaysia.